Auditoria de tecnologia da informação na administração pública no âmbito dos Municípios do Estado do Rio de Janeiro - Monteiro, Gustavo Bastos (2008)
The diffusion of results-oriented management doctrines has been leading the public organizations to make important investments in information technology as a component of transparency for government actions and support for decisionmaking by public administrators. The intensive use of information technology in an increasingly interconnected world exposes the government to new forms of threats and vulnerabilities. In this context, the Courts of Accounts must expand the scope of their acting, performing more stringent controls through specific technics in information technology (IT) audit to ensure the integrity and security of data that travei across networks and information systems. The purpose of this research consisted to identify main improprieties associated with the use of computers in the local public administrations under the jurisdiction of TCE-RJ, by means of the case study of its experience in the accomplishment of performance audit in information technology. The research is based on the literature and analysis of findings from systems audits, showing that this kind of audit has contributed to making local public administration more efficient, effective and transparent.